2013
DOI: 10.1038/aja.2013.65
|View full text |Cite
|
Sign up to set email alerts
|

Obesity leads to higher risk of sperm DNA damage in infertile patients

Abstract: There has been a growing interest over the past few years in the impact of male nutrition on fertility. Infertility has been linked to male overweight or obesity, and conventional semen parameter values seem to be altered in case of high body mass index (BMI). A few studies assessing the impact of BMI on sperm DNA integrity have been published, but they did not lead to a strong consensus. Our objective was to explore further the relationship between sperm DNA integrity and BMI, through a 3-year multicentre stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
113
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(121 citation statements)
references
References 23 publications
1
113
1
6
Order By: Relevance
“…Recently, both clinical and experimental reveal the negative consequences of obesity on male reproductive function. According to the clinical investigation, men with overweight or obesity can decrease sperm quality including sperm concentration, sperm motility, acrosome reaction decline, increased sperm DNA damage and lower embryo implantation rates as well, comparing to those of normal BMI men (Jensen et al 2004, Dupont et al 2013, Samavat et al 2014, Shukla et al 2014, McPherson et al 2015, Soubry et al 2016. In consequence, obesity was associated with a more than 20% increased cases of subfertility and infertility (Cui et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, both clinical and experimental reveal the negative consequences of obesity on male reproductive function. According to the clinical investigation, men with overweight or obesity can decrease sperm quality including sperm concentration, sperm motility, acrosome reaction decline, increased sperm DNA damage and lower embryo implantation rates as well, comparing to those of normal BMI men (Jensen et al 2004, Dupont et al 2013, Samavat et al 2014, Shukla et al 2014, McPherson et al 2015, Soubry et al 2016. In consequence, obesity was associated with a more than 20% increased cases of subfertility and infertility (Cui et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although controversial, numerous studies show that the quality and quantity of male spermatozoa decline from 1 year to the next [2], with many factors including environmental effects, metabolic dysfunction, and genetic polymorphisms apparently associated with a decline in male reproductive ability [3]; however, only obesity has been shown conclusively to be involved in this phenomenon [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested little relationship between the functional competence of spermatozoa, in terms of their ability to bind to the zona pellucida, and BMI (Sermondade et al 2013a), although a recent metaanalysis has revealed odds ratios for oligozoospermia/ azoospermia of 1.28 (1.06-1.55) for obese and 2.04 (1.59-2.62) for morbidly obese men (Sermondade et al 2013b). A more consistent feature of obese males is the appearance of DNA fragmentation in the spermatozoa in association with oxidative stress (Palmer et al 2012a, 2012b, Dupont et al 2013. The DNA damage associated with obesity may be initiated at the spermatid stage of development while spermatids are differentiating into spermatozoa in a process known as spermiogenesis.…”
Section: Obesitymentioning
confidence: 99%